Vacancies in Vacaville... - Porter, Tim (American Journalism Review, 2003)
Focuses on the small-town newspaper 'Vacaville Reporter' in Vacaville, California. Background on smalltown newspapers in the U.S. Role of smalltown newspapers in the development of journalists; Projects covered by 'Vacaville Reporter'; Experiences of Tanya Mannes as a reporter for 'Vacaville Reporter'; Discussion on journalism education in the country, including enrollment in journalism school.